Translation and Historiography: How an Interpreter Shaped Historical Records in Latter Han China - Lung, Rachel (TTR)

(untitled) (Association canadienne de traductologie, 2006)
AbstractThis article analyzes evidence of interpreting activities in first-century China between the Latter Han (25–220 AD) Chinese administration and non-Han Chinese minority tribes along the then Southwestern frontier (modern Yunnan and the west of Sichuan basin). Besides confirming the existence of interpreting events and the subsequent Chinese translation of three tribal sung poems, a tribal tribute to Emperor Ming (r. 58–75) in a Qiang dialect (without a written language, apparently), this piece of evidence is also of interest to historians of interpreting in four aspects, namely, the nature of interpreting activities in China in antiquity; possible political rewards for the amateur interpreter who was a frontier clerk by profession because of possible translation manipulation; textual traces from the Chinese translation of the poems that suggests a possible manipulation in meaning and style; and the (interpreter’s) superior’s part in the manipulation of the translation, which eventually found its way into the standard history of the Latter Han dynasty. Considering the political needs of Latter Han China to promote the Sinicization cause among non-Han tribesmen in the empire, this article argues, based on analyses of the four factors above, that the interpreter, with his rare knowledge of the tribal tongue in the imperial court, might have consciously shaped the translation of the poems to pander to the liking of his superior and the emperor. This article further shows how and why the interpreter, in his official capacity as a frontier clerk, might have capitalized on his competence in a tribal language and manipulated, albeit mildly, the historical records on the Chinese translation of the poems.